Nutritional status indicator and its correlation with mental health score among adolescents in Islamic boarding schools - Luh Ade Wiradnyani; Soraya Ningrum NP Nauli; Saptawati Bardosono (World Nutrition Journal, 2021)
Background: It has been estimated that about 10â€“20% of adolescents worldwide had experiences of mental health problems.Â Malnutrition, including overweight and obese, is one of the risk factors for mental health in adolescents. There is a knowledge gap regarding the nutritional status and its correlation with mental health among adolescents who live in boarding schools. This study aimed to determine nutritional status and its correlation with mental health among adolescents in Islamic boarding schools.Methods:Â Â A cross-sectional approach was used in this study in which two schools in South Tangerang City of Banten Province were purposively selected and 302 of students aged 15â€“18 years were completed this study. BMI-for-age Z-scores (BAZ) was used as the nutritional status indicator, and the Strengths and Difficulties Questionnaire (SDQ) was used to determine mental health of the subjects. Spearman correlation was used to determine the correlation between nutritional status indicator and mental health score.Results: Nearly 30% of the subjects were overweight and obese, and almost 20% had result of mental health score in categories â€œborderlineâ€ and â€œabnormalâ€. There was a significant correlation between nutritional status indicator and mental health score among adolescents in Islamic boarding schools (r=0.157, P=0.006).Conclusion: Adolescents who had higher BAZ, had higher total difficulties scores. The schools and policy makers should give attention to nutritional status of the students since it is correlated with mental health.